2008
DOI: 10.1002/art.23597
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2‐specific chemokines mediate leukotriene B4–dependent recruitment of neutrophils to inflamed joints in mice with antigen‐induced arthritis

Abstract: Objective. To investigate the mechanism underlying neutrophil migration into the articular cavity in experimental arthritis and, by extension, human inflammatory synovitis.Methods. Antigen-induced arthritis (AIA) was generated in mice with methylated bovine serum albumin (mBSA). Migration assays and histologic analysis were used to evaluate neutrophil recruitment to knee joints. Levels of inflammatory mediators were measured by enzyme-linked immunosorbent assay. Antibodies and pharmacologic inhibitors were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 39 publications
(58 reference statements)
6
71
0
Order By: Relevance
“…Intra-articular (tibiofemoral joint) injection of mBSA in mBSA-immunized mice induced a significant neutrophil migration to the articular cavity compared with non-immunized mice. The migration peaked 24 h after mBSA challenge (10 g/articular cavity) (18). mBSA-induced neutrophil recruitment was significantly inhibited by anti-IL-23 or anti-IL-17 antibodies (Fig.…”
Section: The Il-23/il-17 Axis Is Essential For the Neutrophil Migratimentioning
confidence: 84%
See 1 more Smart Citation
“…Intra-articular (tibiofemoral joint) injection of mBSA in mBSA-immunized mice induced a significant neutrophil migration to the articular cavity compared with non-immunized mice. The migration peaked 24 h after mBSA challenge (10 g/articular cavity) (18). mBSA-induced neutrophil recruitment was significantly inhibited by anti-IL-23 or anti-IL-17 antibodies (Fig.…”
Section: The Il-23/il-17 Axis Is Essential For the Neutrophil Migratimentioning
confidence: 84%
“…However, the precise mechanism how the IL-23/IL-17 axis induces neutrophil migration in the articular context is unknown. We have reported previously that intra-articular (tibiofemoral joint) injection of antigen (methylated BSA, mBSA) induced a significant neutrophil migration to the articular cavity in immunized mice compared with non-immunized mice (18). Lipid mediators such as prostaglandins, particularly prostaglandin E 2 (PGE 2 ), are commonly found in the synovial fluid of RA patients and clearly are involved in the tissue inflammation observed in these subjects (19,20).…”
mentioning
confidence: 99%
“…The decreased accumulation of neutrophils and joint damage was associated with decreased local production of proinflammatory cytokines, including TNF-a and IL-1b, and neutrophil-active chemokines. It is well established that cytokines are responsible for the initiation and perpetuation of the inflammatory response in RA as well for the facilitation of neutrophil influx at sites of tissue injury (40,41). In this regard, TNF-a has a key role in the pathogenesis of RA (42) and facilitates the influx of leukocytes, which may in turn increase the local production of TNF-a (43).…”
Section: Discussionmentioning
confidence: 99%
“…The chemoattractants CXCL1/KC, CXCL5/LIX and lymphotactin, which were also reduced in paws of anti-C5aR-treated mice 60 h after a single dose, have been demonstrated to be upregulated in both RA synovial tissue/fluid and other murine arthritis models [36,37]. In addition, it is suggested that lymphotactin can exert immunomodulatory effects through MMP release from synovial fibroblasts and cytokine release from macrophages in addition to its chemotactic properties [37].…”
Section: Discussionmentioning
confidence: 99%